The Principle of Believers' Character in Upholding Truth in Accordance with Surah Al-Anfal - Maryam Qonitat (Sekolah Tinggi Ilmu Ushuluddin (STIU) Darul Hikmah, 2024)
Defending the truth is closely linked to supporting God's religion, especially through da'wah and enjoining good while forbidding evil. However, many Muslims lack a clear understanding of the believer’s characteristics in fulfilling this mission. This study explores the guiding principles found in Sûrah Al-Anfâl, which outlines the defining traits of true believers, particularly in times of conflict and moral struggle. Sûrah Al-Anfâl, revealed during a pivotal moment in early Islamic history, presents enduring lessons on faith, perseverance, unity, justice, and reliance on Allah. Using an analytical approach, the study investigates the historical context of the surah and highlights its relevance to contemporary challenges. Key principles identified include firm belief in Allah, patience in hardship, solidarity among Muslims, moral integrity, and strategic trust in divine support. These are discussed regarding Quranic verses and both classical and modern tafsir. The study also draws parallels between the experiences of the Prophet Muhammad ﷺ and today’s believers, offering practical strategies for spiritual development, community engagement, and constructive dialogue. The findings emphasize that defending the truth must be rooted in sincere faith and follow divine guidance to merit divine victory.